Identification of 8-Azaguanine Biosynthesis–Related Genes Provides Insight Into the Enzymatic and Non-enzymatic Biosynthetic Pathway for 1,2,3-Triazole - Hou, Feifei; Wan, Yupeng; Gan, Qi; Xian, Mo; Huang, Wei (Frontiers in Bioengineering and Biotechnology, 2020)
8-azaguanine (1) is a special 1,2,3-triazole containing natural product that possesses potent antibacterial and antitumor activities. In the present study, the entire 8-azaguanine biosynthetic gene cluster (BGC) was located from Streptomyces CGMCC4.1633. Targeted gene disruption, heterologous expression analysis and feeding experiments identified crucial genes for 8-azaguanine production. Moreover, we characterized the structure of two novel metabolites, revealed NO (or reactive nitrogen species) related genes 8-azgA/B and radical SAM enzyme homologous 8-AzgG, verified the non-enzymatic ring formation reaction of 8-azaguanine 1,2,3-triazole. All of the data and presumptions provide insight into the timing and mechanism of the enzymatic and non-enzymatic pathway that produce 8-azaguanine-type 1,2,3-triazole